2016
DOI: 10.17557/tjfc.95532
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation Among Egyptian White Lupin (Lupinus Albus L.) Genotypes

Abstract: Field Evaluation of eighteen lupin genotypes was carried out during 2012/13 and 2013/14 at Giza Agriculture Research Station, Egypt, to assess the genetic variation on phenological parameters. Simultaneously, molecular diversity assessment was performed using 11 SRAP primer pair combinations. High significant differences among genotypes were observed for field performance during the two seasons and their combined data. The Australian genotype 75 B9.10 and landrace Fayed1 recorded the highest seed yield/plant w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
3
7
0
Order By: Relevance
“…This result can be supported by the idea of very recently published research work Lupinus albus L. landraces can grow up to 146 cm tall [12]. In the study carried out by [28] the maximum seed yield per plant was reported as 38. 3g which is more approached to the minimum value of SYP obtained in this research.…”
Section: Discussionsupporting
confidence: 58%
“…This result can be supported by the idea of very recently published research work Lupinus albus L. landraces can grow up to 146 cm tall [12]. In the study carried out by [28] the maximum seed yield per plant was reported as 38. 3g which is more approached to the minimum value of SYP obtained in this research.…”
Section: Discussionsupporting
confidence: 58%
“…Lupine (Lupinus albus L.) is a leguminous plant that is rich in high good quality protein percentage (44%), and seed dry matters like oil and dietary fiber, lupine cultivation reached to 661 thousand hectares in 2013 with Australia, Russian Federation and Ukraine as the world's highest production areas (El-Harty et al 2016). In Egypt, Lupinus is cultivated in different soil types because its agricultural requirements are very low.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, limited number of studies on white lupin molecular diversity are cited in the literature. To the best of our knowledge, genetic diversity using molecular markers has been estimated for local germplasm from Ethiopia [42,52] and Egypt [53].…”
Section: Discussionmentioning
confidence: 99%